Scribal practice and vowel quantity: Homorganic cluster lengthening in Late Old English manuscripts - Mokrowiecki, Tomasz (My University, 2011)
The first part is a thorough review of the publications on orthographic notations used for marking vowel length in English MSS and those on lengthening of short vowels before homorganic clusters. The study has three major aims. First, a thorough review of the literature on the topic presented in the first part of the thesis is intended to show that the traditional descriptions of HCL are to a large extent confusing, incomplete, and incompatible with one another, whereas the studies that have been carried out so far are often based on entirely wrong assumptions about the change and, what is worse, they take the reliability of the Modern English evidence employed for reconstructing the lengthening at face value. Second, it will be shown that, contrary to common belief, vowel quantity of Old English can be reconstructed on the basis of the evidence from some MSS through analysis of their orthographic systems, as it seems that at least some of them were capable of indicating vowel length. In contrast to most of the previous studies, this includes also an analysis of the orthographic systems of two Late Old English MSS in relation to vowel length. The analysis of the orthographic systems preserved in MS Gg. 3.28 (Homilies of Ælfric) and MS William H. Scheide (The Blickling homilies) presented in the second part of the thesis is an attempt to ascertain to what extent both linear and non-linear notations applied by the scribes can be regarded as formal indicators of vowel quantity and then, with this information on hand, to establish as precisely as possible the conditioning environment for vowel lengthening before consonant groups in the analysed texts, which is the third aim of the study. However, the study is not aimed at explaining the cause and mechanism of the lengthening as this would require a survey on a larger scale, which would include a wide range of texts. Such an analysis is of course impossible here mainly due to the limited availability of relevant primary sources.

Przedmiotem dociekań pracy są zmiany fonologiczne zachodzące pod koniec okresu staroangielskiego, które polegały na wzdłużeniu samogłosek krótkich występujących tuż przed grupami spółgłoskowymi o zbliżonym miejscu artykulacji. Badanie zostało wykonane w oparciu o szczegółową analizę zapisu ortograficznego samogłosek długich jak i krótkich w dwóch wybranych manuskryptach okresu późnostaroangielskiego. Pierwszym celem badania jest sprawdzenie w jakim stopniu długość samogłoski odzwierciedlona jest w systemie pisowni języka późnostaroangielskiego. Nadrzędnym celem badania jest jednak ustalenie kierunku tych zmian oraz wyodrębnienie elementów, które podlegały badanym zmianom a także otoczenia fonologicznego, w którym te zmiany zachodziły. Mimo iż badanie oparte jest jedynie na wybranych manuskryptach z oznaczeniami długości samogłosek, to wyniki przeprowadzonych analiz stanowią istotny wkład w badania nad zmianami ilościowymi samogłosek w historii języka angielskiego.
Pisownia a oznaczenia długości samogłosek: Wzdłużenie samogłosek przed grupami spółgłoskowymi w manuskryptach późnostaroangielskich
Wydział Neofilologii: Instytut Filologii Angielskiej
Keywords: Vowel quantity; Długość samogłosek; Homorganic; Grupy spółgłoskowe; Lengthening; Późnostaroangielski; Old English